Synthesis and Characterization of Sodium Lignosulfonate from Teak Wood Sawdust Lignin via Indirect Sulfonation - Anang Mei Adhitama; Basyirotul Hilmi; Sintha Soraya Santi; Susilowati Susilowati; Suprihatin Suprihati (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This study aims to synthesize Sodium Lignosulfonate (NLS) from teak wood lignin through an indirect sulfonation method. The effect of pH and sulfonation time on the characteristics of the synthesized product was investigated. The sulfonation process was carried out using a sulfonating agent under controlled conditions with variations in pH and reaction time. The obtained product was characterized using Fourier Transform Infrared (FTIR) spectroscopy to identify functional groups and Ultraviolet-Visible (UV-Vis) spectroscopy to evaluate absorbance behavior. The FTIR results indicated the presence of sulfonate groups (-SO?), confirming the successful formation of sodium lignosulfonate. Meanwhile, UV-Vis analysis showed variations in absorbance corresponding to changes in pH and sulfonation time, indicating differences in the degree of sulfonation. The results were compared with previous studies and showed consistent characteristics of sodium lignosulfonate. This study demonstrates that pH and sulfonation time significantly influence the properties of the synthesized product.